Aktivitas Protektif Ekstrak Etanol Daun Ketul (Bidens pilosa L) terhadap Paru-Paru Tikus Putih (Rattus norvegicus) yang Diberi Alkohol - Windah, Putri; Silitonga, Melva; Sinaga, Erlintan; Pranoto, Hendro; Pohan, Selvia Dewi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the protective potential of Bidens pilosa L. leaf ethanol extract against histological damage to the lungs of white rats (Rattus norvegicus) due to alcohol exposure. This study is an experimental research using five treatment groups, consisting of a negative control, a positive control (alcohol), and three groups administered alcohol combined with Bidens pilosa L. leaf ethanol extract (EEDK) at varying doses. The parameters observed include edema, alveolar septum destruction, and inflammatory cell infiltration in lung histology specimens. Data were analyzed using one-way ANOVA followed by DMRT. The results showed that EEDK administration significantly reduced lung damage, as indicated by a decrease in the average damage score from 43.12 ± 0.18 in the alcohol group to 33.92 ± 1.65 (250 mg/kgBW), 23.32 ± 2.18 (500 mg/kgBW), and 14.88 ± 1.06 (750 mg/kgBW). The reduction in lung damage included improvement in edema, reduction in alveolar septal destruction, and suppression of inflammatory cell infiltration. These findings suggest that ethanol extract of Bidens pilosa L. leaves has potential as a natural protective agent through its anti-inflammatory and antioxidant activities, thereby potentially useful for preventing or reducing alcohol-induced lung damage.